Data-Based Leadership: The Role of HR in Strategic Decision-Making in The Furniture Industry, Cirebon Regency, West Java, Indonesia - Rizki, Dwiki Fatur (Green Publisher Indonesia, 2025)
Data-driven HR leadership is crucial for strategic decision-making, yet its implementation in Indonesia’s furniture industry remains understudied. This research examines data-based HR practices at Agung Jaya Putra Furniture, identifying challenges and opportunities in recruitment, performance evaluation, and workforce planning. A qualitative case study was conducted using interviews, observations, and document analysis, with data interpreted via the Miles and Huberman model. Results indicate strong data use in recruitment (78%) but weaker adoption in performance evaluation (65%) due to low data literacy. Workforce planning (72%) relies on historical data but lacks predictive analytics. Challenges include limited digital infrastructure and resistance to change, aligning with Anwar (2022) and Yusuf et al. (2024). Academically, this study enriches HRM literature in SME contexts; practically, it recommends investing in training and cloud-based analytics. The findings highlight the need for cultural and technological shifts to maximize data-driven HR’s potential, offering a roadmap for similar industries.